The courage to change : hope and help for alcoholics and their families : personal conversations with Dennis Wholey - Wholey, Dennis, 1937-; Bauman, Robert, 1937- (Boston : Houghton Mifflin, 1984)
Personal conversations with Dennis Wholey and members of alcoholics anonymous.
13 21 26
Keywords: Alcoholism; Alcoholics -- Rehabilitation -- United States -- Biography